Brexit and the Cost of Living: A Tale of Two Phases - Federico Di Pace; Giacomo Mangiante; Riccardo M. Masolo (Birkbeck, University of London, Birkbeck Centre for Applied Macroeconomics (BCAM), 2025)
We employ Synthetic Control Method techniques to estimate the causal effect of Brexit on the consumer price index (CPI) in the United Kingdom. We construct a counterfactual CPI index from a weighted pool of comparable economies and find that the price level of the United Kingdom rose approximately 7 percentage points more than its synthetic counterpart, between 2016Q2 and 2024Q4. This accounts for over a quarter of total inflation during the period. We attribute about 2 percentage points of this increase to the depreciation of the British pound after the Referendum and the remaining 5 percentage points to the change in trading relationships that ensued the 2021 Trade and Cooperation Agreement.
Keywords: C32; E31; F13; G10; 330; Brexit; Exchange Rate; Trade Barriers and Consumer Prices